Повышение качества распыла технологических жидкостей в энергетических установках - Кравченко, О. В.; Суворова, И. Г.; Баранов, И. А. (Eastern-European Journal of Enterprise Technologies, 2009)
The spray quality of technological liquids determines the efficiency of many technological processes of power plants production and work. The questions related to possibility of quality improvement of technological liquids spray above all things fuels different fuel emulsions and slurries are considered